COAT OF ARMS, FLAG AND ANTHEM OF THE REPUBLIC OF SERBIA: PROTECTION TROUGHT MISDEMEANOR LIABILITY - Dinić, Nikola (National interest, 2024)
The coat of arms, flag and anthem are the bearers of national identity, and their legal regulation and protection would be of particular interest to every country. Serbian identity wandering in the 20th century is also reflected in the arrangement of state symbols and the insufficiently arranged manner of their use. With the adoption of the Law on the Appearance and Use of the Coat of Arms, Flag and Anthem of the Republic of Serbia in 2009, a certain step forward was made in the sense that this law regulates the symbols that represent the Republic of Serbia, the basic rules on displaying the coat of arms and the flag, restrictions on their uses, their appearance, the anthem and the occasions when the anthem is performed, as well as the penal provisions for non-compliance with the provisions prescribed by this law. However, despite this, the matter concerning state symbols is still not adequately regulated in terms of misdemeanor liability of a certain category of persons: possible perpetrators of misdemeanors, thus leaving the possibility for abuses, i.e. for unpunished violation of legal provisions concerning the protection of state symbols. This primarily refers to the category of legal entities as subjects of violations, namely the Republic of Serbia, territorial autonomy and local self-government units and their bodies.